Atrial fibrillation prevalence and risk profile from novel community-based screening in Thailand: A prospective multi-centre study. (February 2021) - Suwanwela, Nijasri C.; Chutinet, Aurauma; Autjimanon, Hathairat; Ounahachok, Tanawat; Decha-umphai, Chumpol; Chockchai, Songkhram; Indrabhakti, Saowanin; Kijpaisalratana, Naruchorn; Akarathanawat, Wasan; Travanichakul, Suporn; Kitjavijitre, Teeraparp; Vongvasinkul, Pakkawan; et al.
Abstract: Background: In Thailand, almost one-quarter of strokes are related to atrial fibrillation (AF), and many could be prevented if AF were diagnosed and treated prior to the stroke. Therefore, we tested a novel strategy to screen large numbers of community residents using village health volunteers and primary care nurses. Methods: Local primary care nurses and village health volunteers in Phetchaburi and Lopburi provinces, Thailand were trained to perform AF screening using a blood pressure device with AF algorithm (Microlife A200 AFib). 10% of residents aged ≥ 65 years were randomly selected for screening during home-visits. Participants with possible AF were given follow-up appointments for further testing, including 12-lead ECG and echocardiogram. Results: Over two-months, 9.7% (13, 864/143, 478) of the target population were screened: mean age 73.2 ± 6.4 years, 32.4% male. The estimated AF prevalence (detected by Microlife A200 AFib) was 2.8% (95% CI, 2.6–3.1%) for age ≥ 65 years (i.e. 393/13, 864 participants). Prevalence increased with age from 1.9% (65–69 years) to 5.0% (≥85 years) (p < 0.001). Only 58% (226/393) of participants with suspected AF attended the follow-up appointment (1–3 months after initial screen): mean CHA2DS2-VASc score 3.2 ± 1.2; 86.3% (195/226) had Class-1 oral anticoagulation recommendation, and 33% (75/226) had AF on 12-lead ECG. Conclusions: In Thailand, large-scale AF screening in the community is feasible using trained volunteer health workers, allowing screening of large numbers in a short time-period. Further investigation of this strategy is warranted, ensuring mechanisms to obtain a timely rhythm strip or 12-lead ECG locally, and a designated pathway to treatment.